Intrabronchial Infusion of Autologous Blood Plus Thrombin for Intractable Pneumothorax After Bronchial Occlusion Using Silicon Spigots: A Case Series of 9 Patients With Emphysema. Issue 3 (July 2016) - Mizumori, Yasuyuki; Nakahara, Yasuharu; Kawamura, Tetsuji; Sasaki, Shin; Tsukamoto, Hiroaki; Mochiduki, Yoshiro
Abstract : Background: Bronchial occlusion therapy using silicon spigots is effective for intractable pneumothorax. However, sometimes the pneumothorax is refractory to bronchial occlusion because of collateral ventilation. For such difficult pneumothoraces, we attempted an intrabronchial infusion of autologous blood plus thrombin to control collateral ventilation and stop air leaks. Methods: We performed bronchial occlusions using silicon spigots in patients with spontaneous pneumothorax secondary to emphysema and refractory to chest drainage, but which was inoperable owing to each patient's poor surgical candidacy and poor overall health condition. When bronchial occlusion proved ineffective, we undertook intrabronchial infusion of autologous blood plus thrombin, 2 to 4 days after bronchial occlusion. A catheter was inserted into the subpleural area, through a gap between the silicon spigot and the bronchial wall, using a flexible bronchoscope under fluoroscopic guidance. Autologous blood, followed by a thrombin solution, was infused using the catheter. We repeated the same infusion a total of 4 to 6 times while changing the target bronchi. All interventions were performed under local anesthesia. Results: The subjects were 9 men, aged from 61 to 88 years, with smoking histories. Three patients also had interstitial pneumonia, and 6 patients had undergone pleurodesis in vain before bronchial occlusion. For 4of the 9 patients, autologous blood plus thrombin infusions successfully stopped air leaks, and in 3 patients, intrabronchial infusions and pleurodesis halted leaks altogether. Conclusion: Intrabronchial infusion of autologous blood plus thrombin was effective for intractable pneumothoraces that could not be clinically managed, even by bronchial occlusion using silicon spigots.